A nefrotoxicidade da polimixina B - Mezzomo, Regina (2022)
Polymyxin B is part of an ancient class of antimicrobials used to fight infections originating from multidrug-resistant gram-negative bacteria. Despite being a great treatment option, it has a cytotoxic profile that affects renal cells, with nephrotoxicity being one of the most limiting adverse events due to the dose and the worsening of the clinical condition of affected patients, triggering acute kidney injury in the vast majority of cases. . In this context, an integrative review was carried out, with the objective of evaluating the scientific literature on the nephrotoxicity of polymyxin B and the consequences caused to individuals who are affected by kidney damage after the use of the antibiotic. Scientific articles were selected from the PUBMED database, using “Polymyxin B AND nephrotoxicity” as descriptors and with a time span of 5 years. From the review, it was found that acute kidney injury induced by polymyxin B nephrotoxicity generates significant impact on adult or pediatric patients, such as longer hospitalization, long-term consequences and increased risk of mortality. Discontinuing the antimicrobial proved to be the most effective option to manage kidney damage, but, in fact, the best way to preserve the integrity of kidney function is to avoid toxic events through follow-up, strict assistance to individuals and not using concomitant polymyxin B to other nephrotoxic agents during this period. In pediatric patients, the incidence of nephrotoxicity is high and therefore treatment with polymyxin B should be an option in last cases with intense monitoring.